Corumbella and in situ Cloudina in association with thrombolites in the Ediacaran Itapucumi Group, Paraguay - Warren, Lucas V. (2011)
An in situ assemblage of Cloudina, thrombolites and an ichnofossil (cf. Archaeonassa), together with fragments of Corumbella werneri, is reported here, from a tidally influenced, shallow, lagoonal setting on a carbonate ramp within the Itapucumi Group, Paraguay. The association of Cloudina with thrombolites is comparable to other terminal Neoproterozoic occurrences, but the coexistence of shelly fossils in situ with trace fossils and microbially induced sedimentary structures is apparently unique. This discovery extends the record of Cloudina and Corumbella in South America and further elucidates the diversity, distribution and palaeoecology of shelled organisms in late Ediacaran time. © 2011 Blackwell Publishing Ltd.